Green Tax Indonesia Untuk Keberlanjutan Lingkungan Hidup: Studi Komparasi Global - Putri, Cantika Primalia Kurnia; Bandiyono, Agus (Universitas Katolik Soegijapranata, Semarang, 2025)
This research aims to find out how green taxes are implemented in different countries, including how they are implemented in Indonesia, as well as the potential that the government can develop to address sustainability issues. This research uses a qualitative method with a literature review approach based on literature, which is then recorded and synthesized to produce a comprehensive understanding of green tax. The result of this research is that although the rules and forms of green tax implementation are different in each country, they have the same main objectives, namely to reduce carbon emissions, increase resource use efficiency and promote the transition to renewable energy. In the context of implementation in Indonesia, in addition to carbon tax and plastic excise tax, policies such as transport tax and landfill tax can be considered to address environmental issues in Indonesia. In this way, green taxes can not only be a source of government revenue, but can also stimulate innovation, create green jobs and improve environmental quality.